Blood Group Testing - Li, Hong-Yang; Guo, Kai (Frontiers in medicine, 2022)
Red blood cell (RBC) transfusion is one of the most frequently performed clinical procedures and therapies to improve tissue oxygen delivery in hospitalized patients worldwide. Generally, the cross-match is the mandatory test in place to meet the clinical needs of RBC transfusion by examining donor-recipient compatibility with antigens and antibodies of blood groups. Blood groups are usually an individual's combination of antigens on the surface of RBCs, typically of the ABO blood group system and the RH blood group system. Accurate and reliable blood group typing is critical before blood transfusion. Serological testing is the routine method for blood group typing based on hemagglutination reactions with RBC antigens against specific antibodies. Nevertheless, emerging technologies for blood group testing may be alternative and supplemental approaches when serological methods cannot determine blood groups. Moreover, some new technologies, such as the evolving applications of blood group genotyping, can precisely identify variant antigens for clinical significance. Therefore, this review mainly presents a clinical overview and perspective of emerging technologies in blood group testing based on the literature. Collectively, this may highlight the most promising strategies and promote blood group typing development to ensure blood transfusion safety.